Strategi Mitigasi Emisi Metana Pada Ruminansia: Sebuah Tinjauan: Strategi Mitigasi Emisi Metana Pada Ruminansia: Sebuah Tinjauan - Ningrat, Rusmana Wijaya Surya; Hellyward, James (Fakultas Peternakan Universitas Jambi, 2024)
Background: Methane emissions from the digestive systems of ruminants significantly impact global warming. Reviews: This article reviews methane emission mitigation strategies in ruminants, emphasizing the underlying scientific aspects. Methane emissions come from microbial fermentation in the digestive system of farm animals such as cattle, sheep, and goat. Feed type, genetics, and fermentation process affect methane emission levels. Nutrition strategies are becoming the main approach using feed additives such as tannin compounds and vegetable oils that are proven to reduce methane production without reducing livestock productivity. Microbial manipulation in the rumen through probiotics and prebiotics has also shown positive results in reducing methane emissions. Developing advanced monitoring technologies, such as sensors and non-invasive monitoring technology, helps accurately identify and measure methane emissions. It is important to consider economic and social aspects in implementing mitigation strategies. Technology affordability and sustainability strategies for smallholder farmers are key focuses. Overall, a holistic approach that includes nutrition strategies, microbial manipulation, monitoring technologies, and economic-social considerations is expected to significantly contribute to reducing the environmental impact of the ruminant farming sector. This strategy not only provides environmental benefits but also can improve the overall efficiency of livestock production. Thus, efforts to mitigate methane emissions in ruminants are a scientific challenge and include social and economic aspects important to achieving sustainability in the livestock sector.